2016
DOI: 10.1038/srep21608
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Immobilization Strategies to Probe Short Hyaluronan-Protein Interactions

Abstract: Well-controlled grafting of small hyaluronan oligosaccharides (sHA) enables novel approaches to investigate biological processes such as angiogenesis, immune reactions and cancer metastasis. We develop two strategies for covalent attachment of sHA, a fast high-density adsorption and a two-layer system that allows tuning the density and mode of immobilization. We monitored the sHA adlayer formation and subsequent macromolecular interactions by label-free quartz crystal microbalance with dissipation (QCM-D). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…1b ). Besides HA 49 and LAM 50 , other polysaccharides such as xylan, pullulan, dextran or galactan can also be functionalized in the same way 51 55 . The two building blocks were then associated by Cu(I)-catalyzed Huisgen cycloaddition as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1b ). Besides HA 49 and LAM 50 , other polysaccharides such as xylan, pullulan, dextran or galactan can also be functionalized in the same way 51 55 . The two building blocks were then associated by Cu(I)-catalyzed Huisgen cycloaddition as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…QCM-D experiments on the immobilization of alginate (a negatively charged polysaccharide) on Pep-1 SAMs showed mass deposition (Δm = 2807.5 ± 192.5 ng cm −2 ) that was slightly removed upon washing ( Figure S9 fluorescence. [16] In another study, BSA (1 mg mL −1 ) adsorption onto surfaces spin-coated with photoreactive HA (modified with 4-azidoaniline) and UV-crosslinked, monitored by QCM-D, revealed significant levels of albumin adsorption (≈250 ng cm −2 ). The next step was to gain insights on the interactions of HA surfaces with serum proteins, which is key to understand cell behavior on these surfaces.…”
Section: Interaction Of Immobilized Ha With Hyaladherins and Serum Prmentioning
confidence: 98%
“…[11,12] It has been demonstrated that signalling downstream of HA-CD44 interactions can regulate stem cell markers and highlights the role of HA in HNSCC progression. These approaches often require the chemical modification of native HA by biotinylation, [14] conjugation to dopamine, [15] thiolation, [16] azidation, [17] or functionalization of surfaces to allow the covalent attachment of HA. These approaches often require the chemical modification of native HA by biotinylation, [14] conjugation to dopamine, [15] thiolation, [16] azidation, [17] or functionalization of surfaces to allow the covalent attachment of HA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the decreasing size of the lateral distance is small enough to be negligible within the timeframe of our experiments of around hundreds of seconds. The decrease of the thickness of the diffusional boundary layer corresponds to a lower adsorption rate (see eqn (1)). The decrease of this adsorption rate in turn is due to a lower availability of receptors because of their occupation by bound bionanoparticles.…”
Section: Evaluating the Model Framework By Spr Experimentsmentioning
confidence: 99%
“…d(x) is the thickness of the velocity boundary layer. v x (y), eqn (4), is the velocity of the fluid in the velocity boundary-layer region and v e (x), eqn(1) and(2), is the velocity of the fluid in the potential flow region between two velocity boundary layers. Velocity profiles at three different positions are depicted.…”
mentioning
confidence: 99%